Efficacy of laser therapy for temporomandibular disorders: A systematic review and meta-analysis - Yan Zhang; Yingqiu Qian; Kangxin Huo; Jingxin Liu; Xi Huang; Jie Bao (Elsevier, 2023)
Objective: The aim of this systematic review was to evaluate the efficacy of laser therapy in temporomandibular disorders (TMD). Methods: Randomized controlled trials (RCTs) in regard to this issue were searched in electronic databases. Three investigators independently screened the eligible studies, and the quality of the included studies was assessed according to the risk of bias tool recommended by the Cochrane handbook. The primary outcome measure was the degree of pain, reported on a visual analog scale (VAS), and the secondary outcome measures were TMJ function, including maximum active vertical opening (MAVO), maximum passive vertical opening (MPVO), left and right lateral movement (LLE, RLE). Pooled effect sizes were calculated using random effects models and 95% confidence interval (95% CI). Results: A total of 28 randomized controlled trials were included. Laser therapy had a more significant effect in terms of VAS (SMD=﹣1.88; 95% CI=﹣2.46 to﹣1.30; P < 0.00001; I2 =93%), MAVO (MD = 4.90; 95% CI= 3.29-6.50; P < 0.00001; I2 =72%), MPVO (MD=5.82; 95% CI= 4.62-7.01; P < 0.00001; I2 =40%) and RLE (MD = 0.73; 95% CI= 0.23-1.22; P = 0.004; I2 = 0%) as compared to placebo group. However, there was no significant difference in LLE between two groups (MD= 0.35; 95% CI=﹣0.31-1.01; P = 0.30; I2 =0%). Conclusions: Laser therapy can effectively reduce pain but have small effect on improving mandibular movement of TMD patients. More well-designed RCTs with large sample sizes are needed for further validation. And these studies should report detailed laser parameters and provide complete outcome measure data.